Unique Counting Call of a Katydid, Scudderia pistillata (Orthoptera: Tettigoniidae: Phaneropterinae). (17th October 2014) - Villarreal, S. M.; Gilbert, C.
Abstract : The katydid Scudderia pistillata Brunner, 1878 (Orthoptera: Tettigoniidae: Phaneropterinae), is anecdotally called the "counting katydid" because the syllables produced from each wing closure of the male calling song are grouped into phrases, with each successive phrase in the first seven phrases of a calling bout typically possessing one more syllable than the previous phrase. Analysis of <500 recorded male bouts showed that adding syllables to each phrase is stereotypic for the species. Although this aspect of the calls was stereotypical, other aspects of the calls exhibited variability, including the total numbers of syllables and phrases per bout, which were correlated with a male's nutritional condition, as indexed by residual weight. Potential behavioral functions of the counting sequence are discussed.